Effect on the performance of B-series propellers with variation in installation angle of propeller boss cap fin - Yamin, M.; Irawan, R.; Mahandari, C.P.; Anwar, F.K.; Firmansyah, R. (Journal of Naval Architecture and Marine Engineering, 2026)
This study examines the influence of Propeller Boss Cap Fins (PBCFs) on the hydrodynamic performance of B-series propellers by introducing variations in installation angles. While PBCFs are widely recognized for their potential to reduce rotational losses and enhance propulsion efficiency, the specific impact of installation angle variation—particularly in the context of electric-powered vessels—has remained underexplored. To address this gap, the present work focuses on the aerodynamic optimization of PBCFs, varying the installation angle between −5° and 5°, using a NACA4412 airfoil profile within a Computational Fluid Dynamics (CFD) framework. The analysis is conducted using the Reynolds-Averaged Navier-Stokes (RANS) approach with a Grid Independence Test (GIT) performed to ensure numerical accuracy. Validation of the simulation results against available experimental data confirms the reliability of the model. The configuration featuring a 2° PBCF installation angle demonstrates the most favorable performance, yielding an increase in the thrust coefficient (KT) from 0.3719 to 0.3797 and an improvement in open water efficiency (η) by 4.3% relative to the baseline CFD model. Additionally, a maximum efficiency enhancement of 24% is observed when compared to experimental data at an advance coefficient of J = 0.415. The validation results exhibit a maximum deviation of 9.934% at lower rotational speeds, which is within an acceptable range for engineering applications, particularly given the challenges of modeling complex flow phenomena at low Reynolds numbers. The principal contribution of this study lies in its systematic evaluation of PBCF installation angle as a design variable—an area that has received limited attention in existing literature. The findings demonstrate that even minor angular modifications can significantly influence propeller performance. More broadly, this research contributes to the advancement of energy-efficient marine propulsion technologies by offering a validated, CFD-based design methodology. The implications are particularly relevant for the development of sustainable propulsion systems in electric and low-emission vessels, supporting broader efforts to reduce fuel consumption and minimize environmental impact in maritime operations. Journal of Naval Architecture and Marine Engineering, 23(1), 2026, PP. 1-20